Impact of Extracellular pH on Apoptotic and Non-Apoptotic TRAIL-Induced Signaling in Pancreatic Ductal Adenocarcinoma Cells - Hagelund, Sofie; Trauzold, Anna (Frontiers in Cell and Developmental Biology, 2022)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is an important mediator of tumor immune surveillance. In addition, its potential to kill cancer cells without harming healthy cells, led to the development of TRAIL-receptor agonists, which however did not show the desired effects in clinical trials. This is caused mainly by apoptosis-resistance mechanisms operating in primary cancer cells. Meanwhile, it has been realized that in addition to cell death, TRAIL also induces non-apoptotic pro-inflammatory pathways which may enhance tumor malignancy. Due to its late detection and resistance to current therapeutic options, pancreatic ductal adenocarcinoma (PDAC) is still one of the deadliest types of cancer worldwide. A dysregulated pH microenvironment contributes to PDAC development, in which the cancer cells become highly dependent on to maintain their metabolism. The impact of pHe on TRAIL-induced signaling in PDAC cells is poorly understood so far. To close this gap, we analyzed the effects of acidic and alkaline pHe, both in short-term and long-term settings on apoptotic and non-apoptotic TRAIL-induced signaling. We found that acidic and alkaline pHe differentially impact TRAIL-induced responses and in addition, the duration of the pHe exposition represents also an important parameter. Thus, adaptation to acidic pHe increases TRAIL-sensitivity in two different PDAC cell lines, Colo357 and Panc1, one already TRAIL-sensitive and the other TRAIL-resistant, respectively. However, the latter became highly TRAIL-sensitive only by concomitant inhibition of Bcl-xL. None of these effects was observed under the other pHe conditions studied. Both TRAIL-induced non-apoptotic signaling pathways, as well as constitutively expressed anti-apoptotic proteins, were regulated by acidic pHe, but whereas the non-apoptotic pathways were differently affected in Colo357 than in Panc1 cells, the impact on the anti-apoptotic protein levels was similar in both cell lines. In Panc1 cells, adaptation to either acidic or alkaline pHe blocked the activation of the most of TRAIL-induced non-apoptotic pathways. Interestingly, under these conditions also significant downregulation of the plasma membrane levels of TRAIL-R1 and TRAIL-R2 were observed. Summing up, extracellular pH influences PDAC cells' response to TRAIL with acidic pHe adaptation showing the ability to strongly increase TRAIL sensitivity and in addition to inhibiting TRAIL-induced pro-inflammatory signaling.